The effect of calcium dobesilate combined with hypoglycemic drugs in the treatment of cataract NPDR and its effect on fundus microcirculation and blood ICAM-1, MCP-1 and MIF levels - Zhang, Zhao; Wang, XiaoMan; Ge, YiQing; Wu, Xia; Ma, YinChao (Journal of Medical Biochemistry, 2023)
Purpose: To explore the effect of calcium dobesilate combined with hypoglycemic drugs in the treatment of cataract complicated with non-proliferative diabetic retinopathy (NPDR) and its effects on fundus microcirculation, intercellular adhesion molecule 1 (ICAM-1), monocyte chemoattractant protein 1 (MCP-1), and macrophage migration inhibitory factor (MIF).Methods: From March 2019 to January 2021, A total of 114 patients with cataract and NPDR were included, and the patients were assigned into the control and the observation groups by random number table method, with 57 cases/group. The control was given hypoglycemic drugs, and the observation was given calcium dobesilate combined therapy. The therapeutic efficacy, blood glucose and blood lipid levels, fluorescein fundus angiography results, fundus microcirculation indexes, retinal neovascularization-related factors, and ICAM-1, MCP-1, and MIF levels before and after treatment were compared between the two groups.Results: The total effective rate of treatment in the observation was higher vs. the control (P < 0.05); Fasting blood glucose (FBG), 2 h postprandial blood glucose (2hPG), glycosylated hemoglobin (HbA1C), triglyceride (TG), total cholesterol (TC) and low density lipoprotein (LDL) in the observation after treatment were reduced vs. the control (P < 0.05); The number of micro-hemangiomas in the observation after treatment was less vs. the control, and the area of hemorrhage, the area of exudation and the thickness of the yellow plate were smaller vs. the control (P < 0.05); The resistance index (RI) value of the observation after treatment was lower than the control, and the end-diastolic blood flow velocity (EDV) and the peak systolic blood flow velocity (PSV) of the observation were higher vs. the control (P < 0.05). ICAM-1, MCP-1, MIF, vascular endothelial growth factor (VEGF) and insulin-like growth factor-1 (IGF-1) in the observation after treatment were reduced vs. the control, but pigment epithelium-derived factor (PEDF) were higher vs. the control (P < 0.05); one case of gastrointestinal reaction took place in the observation, but no adverse reaction occurred in the control, and no clear difference exhibited in the incidence of adverse reactions between the two groups (P > 0.05).Conclusion: Calcium dobesilate combined with hypoglycemic drugs has good clinical efficacy in the treatment of cataract complicated with NPDR, which can effectively reduce the level of blood glucose and blood lipids, reduce inflammation, and mitigate the microcirculation of branch retinal vein occlusion lesions.
Keywords: Calcium dobesilate; Combination therapy; Cataract with nonproliferative diabetic retinopathy; Fundus microcirculation; Intercellular adhesion molecule 1; Monocyte chemotactic protein 1; Macrophage migration inhibitory factor